Adults with cystic fibrosis and pulmonologists: new training needed to recruit future specialists. Issue 1 (17th January 2019) - Blasi, Francesco; Elborn, J. Stuart; Palange, Paolo
The epidemiology and natural history of cystic fibrosis (CF) is changing. Predicted median survival has increased over the past five decades, from less than 12 to more than 45 years in most Western countries, along with an estimated increase of the number of patients: by 20% in children and by 75% in adults, over the period 2010 to 2025 [1]. The number of adults (age ≥18 years) with CF is already larger than the number of children [2, 3]. This is a consequence of improvements in drug therapies and in the management of patients delivered by multidisciplinary teams in specialised CF centres, resulting in prolonged survival; this will be even more pronounced in the future, thanks to the introduction of new CFTR modulators acting on the dysfunctional CFTR protein in epithelial and other cells. Pulmonologists should take the lead in the management of adults with cystic fibrosis. Considerable efforts in research and education are required to ensure all patients to receive a high standard of care. http://ow.ly/cTCb30n22bF